Serum Sclerostin Level Is Negatively Associated with Bone Mineral Density in Hemodialysis Patients - Jing-Wun Lu; Ru-Jiang Syu; Chih-Hsien Wang; Bang-Gee Hsu; Jen-Pi Tsai (Medicina, 2022)
Background and Objectives: Sclerostin and Dickkopf-1 (DKK1) modulate osteoblastogenesis, but their role in bone loss in hemodialysis (HD) patients is inconclusive. This study investigated relationships among lumbar bone mineral density (BMD), serum sclerostin, and DKK1 in HD patients. Materials and Methods: Blood samples were obtained from 75 HD patients. Dual-energy X-ray absorptiometry measured lumbar BMD of the lumbar vertebrae (L2–L4). Enzyme-linked immunosorbent assay revealed serum sclerostin and DKK1 concentrations. Results: There were 10 (13.3%), 20 (26.7%), and 45 (60%) patients defined as presenting with osteoporosis, osteopenia, or normal BMD, respectively. Age, alkaline phosphatase, urea reduction rate, fractional clearance index for urea, sclerostin level, and percentage of female patients are significantly negatively associated with the lumbar BMD and T-score, while the body mass index and waist circumference significantly positively associated with the lumbar BMD and T-score. Multivariate forward stepwise linear regression analysis indicated that serum sclerostin (β = −0.546, adjusted R2 change = 0.454; p < 0.001), age (β = −0.216, adjusted R2 change = 0.041; p = 0.007), and percentage of female HD patients (β = −0.288, adjusted R2 change = 0.072; p = 0.0018) were significantly negatively associated with lumbar BMD in HD patients. Conclusions: Advanced age, female gender, and serum sclerostin level, but not DKK1, were negatively associated with BMD in HD patients.